The Mysterious C-14 Decline - Broecker, W. (Radiocarbon, 2009)
Fundamental to the field of radiocarbon dating is not only the establishment of the temporal record of the calendar age-radiocarbon age offsets but also the development of an understanding of their cause. Although part of the decline in the magnitude of this offset over the past 40,000 can be explained by a drop in C-14 production rate associated with a progressive increase in the strength of the Earth's magnetic shielding, it is clear that changes in the distribution of C-14 among the Earth's active carbon reservoirs are also required. In particular, the steep 15% decline in the C-14 to C ratio in atmospheric CO2 and surface ocean Sigma CO2,. which occurred in a 3 kyr-duration interval marking the onset of the last deglaciation, appears to require that a very large amount (at least 5000 gigatons) of C-14-deficient carbon was transferred to or within the ocean during this time interval. As no chemical or stable isotope anomaly associated with this injection appears in either the marine sediment or polar ice records, this injection must involve a transfer within the ocean (i.e. a mixing of 2 ocean reservoirs, one depleted in C-14 and the other enriched in C-14). Although evidence for the existence of a salt-stabilized glacial-age abyssal ocean reservoir exists, a search based on benthic-planktic age differences and C-13 measurements appears to place a limit on its size well below that required to account for the steep C-14 decline.
453wfTimes Cited:18Cited References Count:30